Exploring gender-specific correlations between nutritional intake, body composition, psychological skills, and performance metrics in young taekwondo athletes - Samanipour, M. H.; Azizi, M.; Salehian, O.; Ceylan, H. I.; Mielgo-Ayuso, J. F.; Coso, J. D.; Muntean, R. I.; Bragazzi, N. L.; Herrera-Valenzuela, T. (Nutrients, 2025)
Objectives: Taekwondo performance is influenced by a complex and dynamic interplay of physical, nutritional, and psychological factors, all of which contribute to competitive success. However, the gender-specific relationships among these factors in young high-performance athletes remain understudied. This study aimed to fill in this knowledge gap.